Significant reduction in toxicity, BOD, and COD of textile dyes and textile industry effluent by a novel bacterium Pseudomonas sp. LBC1 - Telke, Amar A; Kim, Seon-Won; Govindwar, Sanjay P (Folia microbiologica, 2012)
The 16S rRNA sequence analysis and biochemical characteristics were confirmed that the isolated bacterium is Pseudomonas sp. LBC1. The commonly used textile dye, Direct Brown MR has been used to study the fate of biodegradation. Pseudomonas sp. LBC1 showed 90% decolorization of Direct Brown MR (100 mg/L) and textile industry effluent with significant reduction in COD and BOD. The optimum condition for decolorization was 7.0 pH and 40°C. Significant increase in a activity of extracellular laccase suggested their possible involvement in decolorization of Direct Brown MR. Biodegradation metabolites viz. 3,6-dihydroxy benzoic acid, 2-hydroxy-7-aminonaphthol-3-sulfonic acid, and p-dihydroperoxybenzene were identified on the basis of mass spectra and using the 1.10 beta Shimadzu NIST GC-MS library. The Direct Brown MR and textile industry effluent were toxic to Sorghum bicolor and Vigna radiata plants as compared to metabolites obtained after decolorization. The Pseudomonas sp. LBC1 could be useful strain for decolorization and detoxification of textile dyes as well as textile industry effluent.
Keywords: biodegradace; Pseudomonas; Hydrogen-Ion Concentration; Sewage; Industrial Waste; textilní průmysl; Molecular Sequence Data; Coloring Agents; Sorghum; měření biologické spotřeby kyslíku; průmyslový odpad; půdní mikrobiologie; Biological Oxygen Demand Analysis; molekulární sekvence - údaje; Textile Industry; regenerace a remediace životního prostředí; barvicí látky; Soil Microbiology; Biodegradation, Environmental; Environmental Restoration and Remediation; odpadní vody; koncentrace vodíkových iontů